SOCIAL ENTREPRENEURSHIP FEMINISME ASKOWANI: GOTONG ROYONG KWT MENGEMBANGKAN INDUSTRI KREATIF DI LAMPUNG TENGAH - Santosa, Mustika Edi (Jurnal Studi Gender dan Anak, 2023)
This study aims to analyze the ASKOWANI feminist social entrepreneurship movement model in encouraging KWT mutual cooperation to develop creative industries in Central Lampung. This research is a field research using descriptive qualitative research methods. Sources of data using primary data sources and secondary data sources obtained through interviews and documentation. Based on the research results, the researchers concluded that ASKOWANI's feminist social entrepreneurship movement in encouraging KWT mutual cooperation in developing creative industries in Central Lampung was realized through the production of various processed food products in three Production Houses managed by KWT members and providing space for village women to participate inside it. Apart from that, there is also guidance in the form of training and mentoring from ASKOWANI to KWT members as well as cooperation with various stakeholders to accelerate the acceleration of the development of the creative industries they run, starting in terms of capital, production to marketing. Keywords: Social Entrepreneurship, Feminism, Creative Industries, KWT